2021
DOI: 10.1002/14651858.cd002042.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion thresholds for guiding red blood cell transfusion

Abstract: Transfusion thresholds for guiding red blood cell transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 166 publications
4
155
0
5
Order By: Relevance
“…The findings provide good evidence that transfusions with allogeneic RBCs can be avoided in most patients with hemoglobin thresholds between 7.0 g/dL and 8.0 g/dL. However, existing studies have reported that some subsets of patients may benefit from RBCs to maintain higher hemoglobin concentrations and that future research should focus on these clinical contexts [ 31 ]. A recent study stated that a threshold value of 7 g/dL for RBC transfusion in critically ill patients in the intensive care unit is generally reliable [ 26 ].…”
Section: Discussionmentioning
confidence: 87%
“…The findings provide good evidence that transfusions with allogeneic RBCs can be avoided in most patients with hemoglobin thresholds between 7.0 g/dL and 8.0 g/dL. However, existing studies have reported that some subsets of patients may benefit from RBCs to maintain higher hemoglobin concentrations and that future research should focus on these clinical contexts [ 31 ]. A recent study stated that a threshold value of 7 g/dL for RBC transfusion in critically ill patients in the intensive care unit is generally reliable [ 26 ].…”
Section: Discussionmentioning
confidence: 87%
“…The activation of inflammation during blood transfusion was closely related to the severity of postoperative pain. A meta-analysis also confirmed that the restrictive allogeneic blood transfusion strategy could reduce the perioperative infection rate without increasing the incidence of complications such as cardiac events or mortality ( 34 ). Retrospective analysis of a single central database also confirmed that perioperative blood transfusion was independently associated with poor prognosis in patients with GC ( 35 ).…”
Section: Discussionmentioning
confidence: 90%
“…We defined hypovolaemia as indexed deviation of PDD measured BV from estimated BV≤0.9. After the protocolised preoperative haemodynamic optimisation, insertion of lumbar epidural catheter and BV‐measurements, patients received transfusion with red packed blood cells if Hb <6 mmol l −1 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…After the protocolised preoperative haemodynamic optimisation, insertion of lumbar epidural catheter and BV-measurements, patients received transfusion with red packed blood cells if Hb <6 mmol l À1 . 23,24 After discharge from the PCU, patients were treated according to local guidelines for surgery and until discharge. We obtained information on the level of self-evaluated pain, reported by the Numeric Rating Scale (NRS).…”
Section: Protocol; Preoperative Monitoring and Resuscitationmentioning
confidence: 99%